2022
DOI: 10.1038/s41598-022-23793-7
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of breast cancer and chemotherapy on gut microbiome, cognitive functioning, and mood relative to healthy controls

Abstract: Women diagnosed with breast cancer undergoing chemotherapy experience cognitive impairment, symptoms of anxiety and depression, and physical side effects including disruption in the diversity and community composition of the gut microbiome. To date, there is limited research exploring the associations among these specific challenges. The present cross-sectional study explored the associations of self-reported cognitive functioning, depression, and anxiety symptoms, and gut microbiome diversity and community co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…A study by Aarnoutse et al (2022) identified a significant reduction in species richness (p = 0.042) within the gut microbiomes of estrogen-receptor-positive BC patients undergoing treatment with (neo)adjuvant chemotherapy drugs [37]. A similar trend was observed in patients undergoing chemotherapy, as documented by Bilenduke et al (2022), and concentrations returned to baseline post-treatment [38]. Conversely, Horigome et al (2019) found no notable shifts in gut microbiome composition between chemotherapy-treated BC survivors and non-chemotherapy-treated survivors [39].…”
Section: Microbiome Dynamics In Cancer Managementmentioning
confidence: 59%
“…A study by Aarnoutse et al (2022) identified a significant reduction in species richness (p = 0.042) within the gut microbiomes of estrogen-receptor-positive BC patients undergoing treatment with (neo)adjuvant chemotherapy drugs [37]. A similar trend was observed in patients undergoing chemotherapy, as documented by Bilenduke et al (2022), and concentrations returned to baseline post-treatment [38]. Conversely, Horigome et al (2019) found no notable shifts in gut microbiome composition between chemotherapy-treated BC survivors and non-chemotherapy-treated survivors [39].…”
Section: Microbiome Dynamics In Cancer Managementmentioning
confidence: 59%
“…A study by Aarnoutse et al, (2022) identified a significant reduction in species richness (p = 0.042) within the gut microbiome of estrogen receptor-positive BC patients during treatment with (neo)adjuvant chemotherapy drugs [89]. A similar trend in decreased gut microbiome richness during chemotherapy was documented by Bilenduke et al, (2022), which later returned to baseline post-treatment [90]. Conversely, Horigome et al (2019) found no notable shifts in gut microbiome composition between chemotherapy-treated BC patients and untreated counterparts [91].…”
Section: Treatment Outcomes and Therapy Resistancementioning
confidence: 69%
“…A depleted microbial richness is linked to intensified depression symptoms, heightened fear of cancer recurrence, and the onset of diarrhea in BC patients undergoing chemotherapy [89,90,93]. Chemotherapy-associated cognitive impairment (CACI) is a widely documented side effect in BC patients, with deficits manifesting in memory retention, processing speed, and visuospatial ability [92,[94][95][96].…”
Section: Treatment Outcomes and Therapy Resistancementioning
confidence: 99%
“…The gut is often an unwarranted target of chemotherapeutic agents, with mucositis being a common complication ( 449 ). Women diagnosed with breast cancer undergoing chemotherapy experience disruption in GM diversity and composition, cognitive impairment, and symptoms of stress, such as anxiety and depression ( 450 ).…”
Section: The Relationship Between the Microbiota Hpa Axis And Cognitionmentioning
confidence: 99%